Results of a cross Canada survey of blood film review practice patterns by technologists and pathologists. (31st July 2018) - Barth, David; Good, David
Abstract: Introduction: No common or widely accepted criteria exist for physician review of blood films or for reported standards of physician rate of blood film review. Individual institutions generally have internal criteria for physician review of blood films. To better understand how and why blood film reviews are performed at different institutions across Canada, with a specific interest in physician blood film review, we undertook a survey to assess the current practise patterns of physician review of blood films across Canada. Methods: A 15 question survey was developed and sent to 24 academic, large community and corporate laboratories across Canada by e‐mail to laboratory directors of those institutions. Centres were chosen to include all provinces in Canada and most of the major academic centres. Twenty of the 24 centres responded. Results: The mean rate of physician review of blood films as a percentage of all CBCs processed per day was 4.1% (range 0.35%‐13%) and of all blood films made per day was 28.8% (range 1.9%‐66.5%). Data on factors which might affect physician review rates, physician preferences regarding what percentage of physician blood film review rates is reasonable and physician perspectives on the role of physician blood film review are discussed. Conclusion: This survey reveals that there is varying practise patterns and opinions with respect to blood film review by physicians in Canada.